2018
DOI: 10.5194/angeo-36-1563-2018
|View full text |Cite
|
Sign up to set email alerts
|

Electron mirror branch: observational evidence from “historical” AMPTE-IRM and Equator-S measurements

Abstract: Based on now "historical" magnetic observations, supported by few available plasma data, and wave spectra from the AMPTE-IRM spacecraft, and on as well "historical" Equator-S high-cadence magnetic field observations of mirror modes in the magnetosheath near the dayside magnetopause, we present observational evidence for a recent theoretical evaluation by Noreen et al. (2017) of the contribution of a global (bulk) electron temperature anisotropy to the evolution of mirror modes, giving rise to a separate electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…Because generation of whistler mode waves in electron scale magnetic dips has been reported recently (Huang et al, 2018; Yao et al, 2019), if any further electron scale magnetic dips exist, they may be expected to make small scale whistler mode waves. In addition, the existence of electron mirror mode structures in (ion) mirror mode structures was reported by Treumann and Baumjohann (2018), although it has not been expected because of the much lower growth rate compared with that of whistler mode waves which requires the same type of electron anisotropy ( T ⊥e > T ||e ) for wave growth (Ahmadi et al, 2016; Gary & Karimabadi, 2006). Since the wave number of electron mirror mode structures transverse to B is expected to be much larger than that of (ion) mirror mode structures (Noreen et al, 2017), we expect the generation of electron scale fluctuations in the whistler mode wave source regions, if electron mirror structures exist.…”
Section: Discussionmentioning
confidence: 94%
“…Because generation of whistler mode waves in electron scale magnetic dips has been reported recently (Huang et al, 2018; Yao et al, 2019), if any further electron scale magnetic dips exist, they may be expected to make small scale whistler mode waves. In addition, the existence of electron mirror mode structures in (ion) mirror mode structures was reported by Treumann and Baumjohann (2018), although it has not been expected because of the much lower growth rate compared with that of whistler mode waves which requires the same type of electron anisotropy ( T ⊥e > T ||e ) for wave growth (Ahmadi et al, 2016; Gary & Karimabadi, 2006). Since the wave number of electron mirror mode structures transverse to B is expected to be much larger than that of (ion) mirror mode structures (Noreen et al, 2017), we expect the generation of electron scale fluctuations in the whistler mode wave source regions, if electron mirror structures exist.…”
Section: Discussionmentioning
confidence: 94%
“…Their study shows that although the linear growth rate of the electron mirror mode can be much higher than that of the proton mirror mode, the dynamic importance of the electron mirror mode is insignificant since their influence on magnetic field and particle temperature is negligible. Treumann & Baumjohann (2018) suggested that the quasilinear theory as a saturation mechanism does not apply to the mirror mode in space since the observed amplitudes exceed those predicted by quasilinear theory. Their study using old spacecraft data is motivational for future investigations using the high temporal and spatial resolution data set of the MMS mission.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…But so far there have been few unambiguous observations of their existence because the capability to resolve electron-scale structures has been strongly limited by the insufficient measurement resolution of satellite-borne instrumentation. Using magnetic field data obtained from the spacecraft AMPTE-IRM and Equator-S, Treumann & Baumjohann (2018) presented observational evidence for the electron mirror mode in the Earthʼs magnetosheath. Lowfrequency whistler waves were also observed and were used to diagnose the effect of anisotropic electron temperature on the mirror mode.…”
Section: Introductionmentioning
confidence: 99%
“…One way out of the above mentioned basic physical dilemma between observation and theory may be related to the resonance of bouncing particles in the mirror bubble and the persistent thermal ion-acoustic background noise which is independent of the presence of mirror modes (Rodriguez and Gurnett, 1975;Treumann and Baumjohann, 2018a;Treumann and Baumjohann, 2019). These resonant bouncing particles (we here restrict to electrons, but ions if bouncing could contribute in a similar way as well) form the required condensate for phase transition.…”
Section: Quasi-superconducting Phase Transitionmentioning
confidence: 99%
“…Landau diamagnetic theory (cf., e.g., Huang, 1973) suggests that any finite temperature diamagnetism is macroscopically very small, which is confirmed by simulations (Noreen et al, 2017) which show the saturation amplitude to remain minuscule. The observation of large-amplitude localized quasi-stationary magnetic depletions of (50% (see Treumann and Baumjohann, 2018a, for examples, in high resolution) must be enforced by conditions which are not included in linear or quasilinear theory (Treumann et al, 2004). We do not go into discussing this problem here as it has been the subject of previous publications (cf., Treumann and Baumjohann, 2018b;Treumann and Baumjohann, 2019).…”
Section: Introductionmentioning
confidence: 99%